Bisphosphonate-related osteonecrosis of the jaw: specificities - Paulo, Siri (2014)
Bisphosphonate-related osteonecrosis of the jaws (BRONJ) is a severe complication that has recently emerged in patients treated with intravenous bisphosphonates for malignant diseases. This complication usually presents after a minor local trauma during a dental treatment. Several etiopathogenic mechanisms of this pathological condition have been proposed, but no model can explain all morphological changes observed at the macroscopic and microscopic level. BRONJ is likely to be related to direct toxicity in the bone and soft tissue cells, due to nitrogen-containing bisphosphonates. This review elucidates the clinical indications and mechanism of action of bisphosphonates, reports some clinical diagnostic criteria for BRONJ, describe the histopathological criteria for BRONJ diagnosis, the potential triggering pathways and the available treatment strategies.